Ensnared - Howard, A. G. (Anita G.) (2015)
"Alyssa travels to Wonderland once again to free both her mother and Jeb, and to set right all that's gone wrong"--
Sequel to: Unhinged.
Keywords: Characters and characteristics in literature -- Fiction; Rescues -- Fiction; Supernatural -- Fiction; Characters in literature -- Fiction; Rescues -- Fiction; Love -- Fiction; Young adult fiction; Love stories